Inking Your Insights: Investigating Digital Externalization Behaviors During Data Analysis - Kim, Yea-Seul; Henry Riche, Nathalie; Lee, Bongshin; Brehmer, Matthew; Pahud, Michel; Hinckley, Ken; Hullman, Jessica (Proceedings of ISS 2019, 2019)
Externalizing one’s thoughts can be helpful during data analysis, such as which one marks interesting data, notes hypotheses, and draws diagrams. In this paper, we present two exploratory studies conducted to investigate types and use of externalizations during the analysis process. We first studied how people take notes during different stages of data analysis using VoyagerNote, a visualization recommendation system augmented to support text annotations, and coupled with participants’ favorite external note-taking tools (e.g., word processor, pen & paper). Externalizations manifested mostly as notes written on paper or in a word processor, with annotations atop views used almost exclusively in the initial phase of analysis. In the second study, we investigated two specific opportunities: (1) integrating digital pen input to facilitate the use of free-form externalizations and (2) providing a more explicit linking between visualizations and externalizations. We conducted the study with VoyagerInk, a visualization system that enabled free-form externalization with a digital pen as well as touch interactions to link externalizations to data. Participants created more graphical externalizations with VoyagerInk and revisited over half of their externalizations via the linking mechanism. Reflecting on the findings from these two studies, we discuss implications for the design of data analysis tools.